Interpretative Phenomenological Analysis tentang Resiliensi Pada Tenaga Kesehatan Penyintas Covid-19 - Hamidati, Hilma Kamila; Aulia, Farah (Happiness: Journal of Psychology and Islamic Science, 2023)
Resilience is an important ability possessed by individuals when facing a stressful situation in order to be able to survive and bounce back, including when facing the Covid-19 pandemic and being a Covid-19 survivor. Healthcare workers are one of the professions that are most vulnerable being psychologically affected when handling the Covid-19 pandemic. There are many reasons why Healthcare Workers experience psychological pressures when handling the Covid-19 pandemic; those are increasing workload, changing work situations and techniques, and facing stigma from the community.Those pressures are increased when they become Covid-19 survivors. The Healthcare Workers experienced boredom, stress, and anxiety in their recovery process, and it got worse when their family was also infected with Covid-19 because the healthcare workers were not merely thinking about their own condition but also thinking about their families condition. This study aims to see an overview of the resilience process in Healthcare Workers whose whole family members also become positive Covid-19 survivors. This study used a qualitative method using a phenomenological approach and applied interpretative phenomenological analysis (IPA) for the data analysis techniques. The subjects in this study consisted of three Healthcare Workers Covid-19 survivors who work in one of the Public Health Centre in Payakumbuh, whose whole family became Covid-19 survivors too. This study applied a semi-structured interview technique and used interview guidelines as a data collection method. The results of this study found that the three subjects went through a phase in the process for resilience. In the three subjects, eight themes related to resilience were found, namely Stress Facing, Comprehension of Condition, Concern to Others, Optimism, Coping Strategies, Receive and Adaptation, Support System, and Wisdom.